Drivers of Environmental Disclosure and Stakeholder Expectation: Evidence from Taiwan - Huang, Cheng-Li (Journal of business ethics, 2010)
This article investigates stakeholder expectations associated with corporate environmental disclosure. Several articles have studied the effect that stakeholder pressure has on environmental disclosing strategies. In this article, we extend previous research to an examination of the influence of external, internal, and intermediary stakeholder groups or constituencies in turn to clarify the demands of multiple stakeholders as to firms’ disclosure of sufficient and adequate environmental information. The sample comprised Taiwanese firms listed on the Taiwan Stock Exchange. Our results show that the level of environmental disclosure is significantly affected by stakeholder groups’ demands. External stakeholder groups, such as the government, debtors, and consumers, exert a strong influence over management intentions regarding the extent of environmental disclosure. Internal stakeholder groups, such as shareholders and employees, impose additional pressures on firms to disclose environmental information. As for intermediate stakeholder groups, environmental protection organizations, and accounting firms, these can greatly influence managerial choices regarding their environmental disclosure strategies.